2013
DOI: 10.3109/03639045.2013.828215
|View full text |Cite
|
Sign up to set email alerts
|

Potential technique for tiny crystalline detection in lycopene-loaded SLN and NLC development

Abstract: It could be concluded that TEM is a promising method for detection of low-level crystallinity of solid nanocarriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…According to several studies, it has been reported that when the drug does not exhibit its endothermic peak in the nanostructured formulations, the drug is considered to be in amorphous state (Agrawal et al, 2010;Okonogi and Riangjanapatee, 2014). Thus, it could be concluded that Hes was converted after encapsulation from crystal form to an amorphous state.…”
Section: Resultsmentioning
confidence: 93%
“…According to several studies, it has been reported that when the drug does not exhibit its endothermic peak in the nanostructured formulations, the drug is considered to be in amorphous state (Agrawal et al, 2010;Okonogi and Riangjanapatee, 2014). Thus, it could be concluded that Hes was converted after encapsulation from crystal form to an amorphous state.…”
Section: Resultsmentioning
confidence: 93%
“…Different types of antioxidant compounds have been topically administered in the skin, such as carotenoids [9][10][11][12][13], coenzyme Q10 [14][15][16][17][18], essential oils [19][20][21], polyphenols [22][23][24][25][26], and vitamins [27][28][29][30][31]. Since only a few active ingredients are effective after topical application due to the barrier function of the skin, lipid nanoparticles have been explored as carriers to enhance bioavailability, skin penetration, and retention of the active ingredients [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring waxes like CRW, CLW, and BW have been approved as generally recognized as safe for direct addition to foods and have been used as solid lipid in formulation of SLN and NLC by some researchers (Asumadu-Mensah, Smith, & Ribeiro, 2013;Lacatusu et al, 2013;Mitrea, Ott, & Meghea, 2014). However, the potential of less explored waxes (PW and orange wax) in formation of an appropriate solid lipid matrix was also reported (Okonogi & Riangjanapatee, 2014;Soleimanian, Goli, Varshosaz, & Sahafi, 2018).…”
Section: Formulationmentioning
confidence: 99%
“…Ruktanonchai et al (2008) formulated SLNs using cetyl palmitate for encapsulation of γ-oryzanol as a natural antioxidant for both pharmaceutical and food applications. Other kinds of lipophilic bioactive food ingredients; β-carotene, β-sitosterol, and lycopene have been also successfully encapsulated into wax-based NLC and SLN delivery systems (Lacatusu, Badea, Ovidiu, et al, 2012;Lacatusu, Badea, Stan, et al, 2012;Okonogi & Riangjanapatee, 2014). Nanoencapsulation of lutein in CRW matrix has been reported by Lacatusu et al (2013).…”
Section: Application In Food Industrymentioning
confidence: 99%
See 1 more Smart Citation